Two new species and one new record of the genus Macaduma Walker, 1866 from China (Lepidoptera: Erebidae, Arctiinae) - T. T. Zhao; K. Bucsek; H. L. Han (SHILAP)
In this paper, two new species of the genus Macaduma Walker, 1866: Macaduma huanglianshana Zhao, Bucsek & Han, sp. n. and Macaduma. chenglaiae Zhao, Bucsek & Han, sp. n., are described from Yunnan Province, China. Meanwhile, another species: M. micra Dubatolov & Bucsek, 2016 is reported for the first time from China. Adults of these species are illustrated, and images of the male genitalia are provided.